A Study On Adolescent Obesity And Over Weight : Risk Factors Associated, Vitamin D Status,Covid 19 Impact (Journal of Pharmaceutical Negative Results, 2022)
Background: Adolescent obesity has become alarming health problem reaching epidemic levels world wide,Covid 19 further worsened this scenario. Adolescent obesity is a multifaceted disease with serious immediate, intermediate and long-term consequences on both physical and mental health. So, if not intervened, It could transform into major health problem,there by posing economic challenges for future generations. So, its important to know the risk factors associated .There is limited research relating risk factors, vitamin d status and covid 19 impact.so our study is aimed at this.Methodology: This is a Cross-sectional Observational study conducted in the department of pediatrics MMCHRI, among 100 children included by convenience sampling method, aged 10 to18 years for a period of 1 year during April 2021-april 2022.Results:In our study of 100 study participants 75 were aged 10 to 14 years and 25 in 15 to 18 years . Our studies showed that high screen time contributed 76 % ,sedentary life style 72 % along with fatty food 70 % consumptions are the major risk factors contributing to obesity. 62 % had vitamin deficiency.Conclusion: Our study showed high screen time, sedentary life style along with fatty food consumption are the most important risk factors. COVID-19 pandemic evoked major lifestyle changes including indoor stay reducing out door activity. Schools closed increased online classes further increasing screen time. There was vitamin D deficiency in majority of adolescents in our study. So primary prevention methods should be aimed at educating the child and family and encouraging appropriate diet and exercise from young age. Secondary prevention is by preventing the child from unhealthy habits.Due to the serious implications,effective treatments are urgently needed. Lifestyle interventions represent the recommended therapy.